Ketidakstabilan Negara Jiran dan Kesannya kepada Keselamatan Malaysia - Wan Hassan, Wan Shawaluddin; Othman, Zaini (ASPENSI in Bandung, Indonesia, 2009)
ABSTRACT: Religious and ethnic conflict, secession movements as well as economic downturn are among the many causes that could destabilize a country. Such incapability on the part of the government could in turn leave an impact on neighboring countries. In this context, Malaysia is, however, one of the nation-state that has a good development economically and stable condition politically since 1980s. On the contrary, instabilities in neighboring countries will give impact to Malaysia as a nation-state. By applying weak state concept, this article intends to discuss the development in neighboring nation-state i.e. Indonesia, Thailand and the Philippines and how it could threaten Malaysiaâs security. In this article, âweak stateâ refers to the failure of those in power to provide to its people security from threat domestically or internationally, political institutions, social as well as economic facilities. Instability in one country will have spill over effects on neighboring countries in Southeast Asia region. This article also found that failures in neighboring countries government in Southeast Asia region to deal political, economic and social issues had indeed left an impact to Malaysiaâs security.Key words: weak state, political instability, neighboring countries, and Malaysiaâs development and security.Â Â About the Authors: Wan Shawaluddin Wan Hassan ialah Pensyarah Kanan di Program Hubungan Antarabangsa, Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Beliau dilahirkan di Kota Bharu, Kelantan, pada 28 Jun 1960. Memperolehi ijazah pertama dalam bidang sejarah dari UM (Universiti Malaya) pada tahun 1985; ijazah Sarjana dari Lancaster University (1991) dalam bidang International Relations & Strategic Studies. Bidang penyelidikan beliau ialah dasar luar Malaysia, keselamatan dan migrasi. Hasil karya beliau, di antaranya, adalah: âMalaysia-United States Relations in the 1990sâ dalam Jurnal Kinabalu, Bil.11 (2005) ditulis bersama Diana Peters; dan âPerpecahan Kesatuan Soviet: Tinjauan tentang Punca Keruntuhanâ dalam Jurnal Sejarah, No.13 (2005) ditulis bersama Ramli Dollah. Alamat e-mail beliau adalah: wshawal@yahoo.com Zaini Othman, M.A. ialah Pensyarah Hubungan Antarabangsa di Sekolah Sains Sosial UMS. Beliau dilahirkan di Pasir Mas, Kelantan pada 27hb April 1967. Memperolehi ijazah pertama dalam bidang Sains Politik dari UKM (Universiti Kebangsaan Malaysia) Bangi, pada tahun 1991; dan ijazah Sarjana (M.A.) dari University of Manchester, United Kingdom (1993-1995) dalam jurusan Pembangunan Politik & Ekonomi Politik Antarabangsa. Antara hasil penulisan beliau ialah Demokrasi, Kepimpinan & Keselamatan dalam Politik Malaysia (Bangi: Penerbit UKM, 2006). Beliau juga telah membentang dan menyertai pelbagai seminar, sama ada di peringkat domestik ataupun antarabangsa. Bersabit kepentingan akademik, beliau boleh dihubungi dengan alamat e-mail: znothman@yahoo.comHow to cite this article? Wan Hassan, Wan Shawaluddin & Zaini Othman. (2009). âKetidakstabilan Negara Jiran dan Kesannya kepada Keselamatan Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.1 [Mei], pp.59-74. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (March 22, 2009); Revised (April 25, 2009); and Published (May 20, 2009).